Electrochemical Behavior of Electrode Materials (Nickel and Stainless Steels) for Sudomotor Dysfunction Applications: A Review - Zagal-Moya, J; Zagal-Moya, J (Wiley-VCH Verlag, 2018)
This is an overview of the electrochemical characterization of nickel and stainless steel (so-called SS) as electrodes in medical devices for the early diagnosis of small fiber neuropathy that originates from type-2 diabetes or cystic fibrosis. The electrical current responses obtained during the clinical tests are related to the amount of chloride present on the sweat. SS electrodes are now used to replace nickel because this later not only presents problems with chloride sensitivity but its contact with skin can cause possible allergic reactions for some patients. For the above reasons, several types of SS were studied. It was shown that some of them perform well and have lower costs than Ni electrodes. We discuss the state of the art of the electrochemical studies conducted with nickel and steels under physiological or biomimetic conditions and discuss the advantages of a particular steel over the others depending on the conditions, especially chloride concentration. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim